An organisational performance measurement model based on AHP sensitivity analysis. (4th December 2006) - Wu, Cheng-Ru; Chang, Che-Wei; Lin, Hung-Lung
This research proposes an Analytic Hierarchy Process (AHP) sensitivity analysis to evaluate organisational performance of hospitals. The relative weights of evaluation criteria are determined using the AHP sensitivity analysis, followed by ranking of the hospitals for decision makers to evaluate in medical-related sectors. The AHP sensitivity analysis-based decision-making method is used to construct an evaluation method, which can provide decision makers or administrators of hospital with a valuable reference for evaluating the organisational performance. Consequently, the proposed model can assist the medical sector to assess the organisational performance of hospitals, making it highly applicable for academia and commercial purposes.